Probing the structure of nanodiscs using surface-induced dissociation mass spectrometry - Harvey, Sophie R. (Chem Commun (Camb), 2020)
In the study of membrane proteins and antimicrobial peptides, nanodiscs have emerged as a valuable membrane mimetic to solubilze these molecules in a lipid bilayer. We present the structural characterization of nanodiscs using native mass spectrometry and surface-induced dissociation, which are powerful tools in structural biology.